User-centered design of discharge warnings tool for colorectal surgery patients. (16th March 2017) - Naik, Aanand D; Horstman, Molly J; Li, Linda T; Paasche-Orlow, Michael K; Campbell, Bryan; Mills, Whitney L; Herman, Levi I; Anaya, Daniel A; Trautner, Barbara W; Berger, David H
Abstract: Objectives: Readmission following colorectal surgery, typically due to surgery-related complications, is common. Patient-centered discharge warnings may guide recognition of early complication signs after colorectal surgery. Materials and Methods: User-centered design of a discharge warnings tool consisted of iterative health literacy review and a heuristic evaluation with human factors and clinical experts as well as patient end users to establish content validity and usability. Results: Literacy evaluation of the prototype suggested >12th-grade reading level. Subsequent revisions reduced reading level to 8th grade or below. Contents were formatted during heuristic evaluation into 3 action-oriented zones (green, yellow, and red) with relevant warning lexicons. Usability testing demonstrated comprehension of this 3-level lexicon and recognition of appropriate patient actions to take for each level. Discussion: We developed a discharge warnings tool for colorectal surgery using staged user-centered design. The lexicon of surgical discharge warnings could structure communication among patients, caregivers, and clinicians to improve post-discharge care.